Dealing with vascular anomalies during radial forearm free flap harvest: report of two cases and review of the literature. Issue 12 (December 2019) - Breik, O.; Selbong, U.; Laugharne, D.; Jones, K.
Abstract: Radial forearm free flap reconstruction for head and neck cancer is very common, and it is widely considered a workhorse flap. Although this flap has a relatively reliable anatomy, surgeons need to be aware of possible anatomical variations and how to deal with them. This paper presents the cases of two patients who underwent oral reconstruction, in whom anomalies of the radial artery were identified while raising a radial forearm free flap. Case 1 demonstrates the dominant branch of the radial artery joining the common interosseous artery approximately 9 cm from the first wrist crease. Case 2 demonstrates abnormal distal branching of the radial artery approximately 4 cm from the first wrist crease. Reconstruction with the flap was successful in both cases. A literature review of reported anomalies of the radial artery is presented, and how to deal with such vascular anomalies is discussed.